Strengthening academic bridges: MoU between ASAINDO and UiTM's Faculty of Hotel and Tourism Management - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
A significant milestone was marked on 21 June 2025 with the signing of a Memorandum of Understanding (MoU) between ASA Indonesia University (ASAINDO) and the Faculty of Hotel and Tourism Management, UiTM. The ceremony took place at Sri Alam Hall, located within the faculty, and was attended by academic leaders, faculty members, and representatives from both institutions. This MoU signifies a formal commitment to fostering academic cooperation, particularly in the areas of hospitality, tourism, and related research initiatives. The collaboration aims to promote student and staff mobility, joint research projects, curriculum development, and knowledge exchange. ultimately enhancing the global outlook and academic excellence of both institutions.